PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, DISIPLIN KERJA DAN FASILITAS SEKOLAH TERHADAP SEMANGAT KERJA GURU SMP HANG KESTURI MEDAN - Guslihati Nasution; Zainuddin Zainuddin; Erwin Pardede (JURNAL PROINTEGRITA, 2021)
Teacher morale can be increased by improving the factors that can influence it. But what is discussed in this study is limited to the factors of principal leadership, work discipline and school facilities. This study aims to determine the effect of the principal's leadership, work discipline and school facilities simultaneously on the morale of teachers of SMP Hang Kesturi Medan. The population of this research is 34 teachers. To determine the number of samples used saturated samples so that the sample is 34 people. Data collection techniques in this study were questionnaires, interviews and documentation studies. While the data analysis technique used is the classical assumption test, multiple regression, t test, F test and the coefficient of determination. The results showed that the leadership of the principal had an effect on the morale of the teachers at SMP Hang Kesturi Medan. There is a positive influence where the better the leadership of the principal, the higher the morale of the teacher will be. This means that teacher morale can be increased by improving the leadership of the principal. Work discipline affects the morale of teachers at Hang Kesturi Middle School Medan. There is a positive influence where the better the work discipline, the higher the morale of the teacher. This means that teacher morale can be increased by improving work discipline. School facilities have an effect on the morale of teachers of SMP Hang Kesturi Medan. There is a positive influence where the better the school facilities, the higher the morale of the teachers. This means that teacher morale can be improved by improving school facilities. Simultaneously there is a significant influence of the principal's leadership, work discipline, school facilities on teacher morale. It is suggested that the principal should be more active in empowering parents and community members, schedule visits to other schools to increase cooperation in the education sector, seek to obtain funds for additional school facilities, and involve staff in managing school resources. It is advisable for the disciplined teacher to note important things in the teaching and learning process and the discipline of completing work according to the specified time. School facilities that need to be repaired with classroom decorations that provide an atmosphere of enthusiasm for learning, use props when delivering subject matter, and maintain the beauty of the school garden. The morale of the teacher can still be improved by improving the quality of teacher results in accordance with the set standards, namely planning learning techniques to improve the abilities of students. Further research is needed by other studies by examining more independent variables on teacher morale.